STRATEGI KOPING PASIEN DIABETES MELITUS PASCA AMPUTASI (STUDI FENOMENOLOGI) - Putri Sari Nugrahaning Dewi (Poltekkes Kemenkes Jakarta III, 2016)
Diabetic patients have a higher risk of amputation in the lower extremity due tovascular complications caused. All surgical procedures including surgicalamputation have impacts on the patients such as stress, which is due to functionallimitations after amputation. This study aimed to know the coping strategies andimpacts of amputation experienced by the diabetic patients in Bangetayu publichealth center, Semarang city. Participants were selected by snowball samplingtechnique. Unstructured interviews and observations were used in the datacollection. The data were analyzed using Colaizzi steps which includes obtaininga clear picture of the phenomenon, taking notes of the obtained data, reading thetranscript repeatedly, determining the meaning of each statement, compiling datainto themes and categories, integrating the results into a narrative description,and doing validation to the participants. This study resulted in four major themeswhich include the impacts experienced by the patients, coping resources, forms ofsocial support, and coping strategies. The impacts which the patients experiencedinclude physical, activity, and psychological impacts. The social support wasreceived from the family and health care workers, and the coping strategies usedwere problem focused coping and emotional focused coping.